Biomedical and Ontological Transformation of Death Into Sickness - Álvarez González, Carlos Fernando; Hernández Albarracín, Juan Diego; Pallarès Piquer, Marc (Revista de Filosofía, 2020)
This piece seeks to present some origins of the biomedical transformation and ontological of death -as an ontological determinant- into sickness, a step that will be possible thanks to the advancements in medicine and biotechnology. From that exposition, the contributions of Craig Venter, María Blasco, Raymond Kurzweil, and Nick Bostrom about the control and overcoming of aging, robotic humanizations, and constant improvement of human life limitations in front of its determinant possibility (finitude). Those issues were studied from the philosophical platform that Martin Heidegger expresses in Being and Time, where he understands death as the most proper, irrespective, and unavoidable possibility the Dasein must face. Finally, the problem of death with senescence in its current state is articulated. The article promotes, in conclusion, new propositions to prosecute the characterization of this biomedical and ontological transformation of death -as an ontological determinant- into sickness.